Biomineralization technology for solidification/stabilization of heavy metals in ecosystem: status and perspective - Li, Shuang; Wu, Xiang; Xie, Jiamin (Frontiers in Ecology and Evolution, 2023)
Biomineralization technology offers an eco-friendly and efficient method for stabilizing heavy metals (HMs) in ecosystem. This technology comprises two primary methods: microbially induced carbonate precipitation (MICP) and enzyme-induced carbonate precipitation (EICP). Biomineralization provides a superior alternative to stabilize heavy metals due to its low energy consumption, reduced carbon dioxide emissions, and superior biocompatibility. In the process of biomineralization, heavy metal ions precipitate and co-precipitate with calcium carbonate, forming a solidified and stabilized product. Despite its many advantages, little attention has been paid to the impact of biomineralization on mitigation of ammonia nitrogen of bio-treated polluted water and the strength of contaminated soil, limiting its further applications in ecological environment restoration. This paper summarizes recent advancements in biomineralization for solidifying and stabilizing (S/S) heavy metals in contaminated water and soil. Key factors inhibiting this method's application include the concentration and combinations of heavy metal ions, the concentration of ammonia nitrogen in polluted water, and the properties of contaminated soil. Finally, this paper offers recommendations on the optimization of further research and experimental design of biomineralization on S/S polluted water and contaminated soil.